Collision dynamics analysis of lifting the pantograph. (April 2021) - Yao, Yongming; Zhou, Ning; Zou, Dong; Mei, Guiming; Zhang, Weihua
An extended pantograph-catenary (PAC) contact collision model is presented in this paper. The catenary is described by a finite element model while the pantograph is described by a multi-body model. The normal collision model is established by using the Hertzian contact theory. A 1:1 PAC collision contact test rig is built to validate the pantograph-lifting model. The dynamic responses of the PAC system during lifting the pantograph with different velocities and positions are studied. The research results show that the velocity and position of lifting the pantograph will affect the pantograph-lifting time, acceleration of collector piece, vertical displacement and contact force in the process of lifting pantograph. When the velocity of lifting the pantograph exceeds 0.5 m/s, the contact force between the pantograph and the contact wire will exceed 250 N, which is the allowed value set in the provisions of EN50367. It is essential to control the velocity of lifting the pantograph below 0.4 m/s to prevent the catenary or contact piece from being damaged due to the excessive impact force. The distribution of the droppers also affects the collision force between the PAC system.